Childhood Obesity, Endothelial Cell Activation, and Critical Illness - Radman, Monique; McGuire, John; Zimmerman, Jerry (Frontiers in Pediatrics, 2020)
Pediatric obesity is increasing in prevalence and is frequently an antecedent to adult obesity and adult obesity-associated morbidities such as atherosclerosis, type II diabetes, and chronic metabolic syndrome. Endothelial cell activation, one aspect of inflammation, is present in the early stages of atherosclerosis, often prior to the onset of symptoms. Endothelial activation is a pathological condition in which vasoconstricting, pro-thrombotic and proliferative mediators predominate protective vasodilating, anti-thrombogenic and anti-mitogenic mediators. Many studies report poor outcomes among obese children with systemic endothelial activation. Likewise, the link between childhood obesity and poor outcomes in critical illness is well established. However, the link between obesity and severity of endothelial activation specifically in the setting of critical illness is largely unstudied. Although endothelial cell activation is believed to worsen disease in critically ill children, the nature and extent of this response is poorly understood due to the difficulty in measuring endothelial cell dysfunction and destruction. Based on the data available for the obese, asymptomatic population and the obese, critically ill population, the authors posit that obesity and obesity-associated chronic inflammation, including oxidative stress and insulin resistance, may contribute to endothelial activation and associated worse outcomes among critically ill children. A research agenda to examine this hypothesis is suggested.